FINDING COMMON GROUND: MORAL VALUES AND CULTURAL IDENTITY IN EARLY CONFLICT OVER THE GRAND STAIRCASE-ESCALANTE NATIONAL MONUMENT (Utah Environmental Law Review; Vol 28 No 2 (2008), 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The south rim of the Grand Canyon in Arizona was bustling with activity on the morning of September 18, 1996.   President Bill Clinton was about to officially announce that he was using his power under the Antiquities Act of 1906 to reserve 1.7 million acres in southern Utah as the new Grand Staircase-Escalante National Monument (hereafter GSENM or “the monument”).   It would be the first national monument to be managed under the jurisdiction of the Bureau of Land Management rather than the National Park Service.   Amidst the crowd, wilderness advocates and environmentalists assembled in support of the new monument, the designation of which would essentially stymie development of the Kaiparowits coal field and the Andalex mine. Representatives of regional Indian tribes were invited to join the celebration, but few attended.